Calculation the Cross Sections for 6Li(Î±,p)9Be Reaction by Reverse Reaction (JOURNAL OF ADVANCES IN PHYSICS, 2014)
In this study light elements 6Li , 9Be , 10Be for 6Li(Î± , p)9Be reaction with proton energy from ( 27.5) MeV to ( 67.5 ) MeV with threshold energy (2.3626) MeV are used according to the available data of reaction cross sections. The Q-value is equale (2.125MeV) and parity of ( 9Be =3/2+) ,(B =3+) and (Li = 1+) for the ground state .The more recent cross sections data of 6Li(Î±,p)9Be reaction is reproduced in fine steps and by using (Matlab-7.6-2008a) program and get the equation from 3-degree for plotted. We deduced that the high probability to produced 9Be by bombard 6Li by alpha particle